2019
DOI: 10.1002/ima.22347
|View full text |Cite
|
Sign up to set email alerts
|

Neuro‐wavelet based intelligent medical image fusion

Abstract: Imaging based sensitive clinical diagnosis is critically depending on image quality. In this article, the problem of enhancing fundus images is addressed by a novel fusion technique. The proposed approach utilizes the representation capability of wavelet transform and the learning ability of artificial neural networks. In this approach, input images are decomposed into wavelet transform followed by appropriate feature extraction for training of neural networks to obtain fused image. To ensure homogeneity, it e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 69 publications
(100 reference statements)
0
3
0
Order By: Relevance
“…The author's contributed work represents a quality fused image with directionality, and better visualization, and is 35% superior to the state-of-the-art fusion methods such as NSCT, NSST, etc. Mehdi Hassan et al [87] suggested neuro-wavelet based MIF. The low and high frequency coefficients are fused by using the neural network with extracted features.…”
Section: Hybrid and Optimization Algorithms Based Medical Image Fusionmentioning
confidence: 99%
“…The author's contributed work represents a quality fused image with directionality, and better visualization, and is 35% superior to the state-of-the-art fusion methods such as NSCT, NSST, etc. Mehdi Hassan et al [87] suggested neuro-wavelet based MIF. The low and high frequency coefficients are fused by using the neural network with extracted features.…”
Section: Hybrid and Optimization Algorithms Based Medical Image Fusionmentioning
confidence: 99%
“…The image alignment is performed via rotating, shifting, and scaling. The performance instability to the changed data set and color distortion is considered as the important limitations during image fusion 11‐13 …”
Section: Introductionmentioning
confidence: 99%
“…Seal and Panigrahy [18] focused on translation-invariant à trous wavelet transform and fractal dimension using a differential box counting method. Hassan et al [19] implemented image fusion methods that are combined with wavelet transform and the learning ability of artificial neural networks. In recent years, deep learning networks have also been used to execute image fusion [20][21][22].…”
Section: Introductionmentioning
confidence: 99%